Principals’ leadership strategy to improve “link and match” quality for vocational education - Asrin Asrin; Agus Ramdhani; Lalu Muhaimi; Mohammad Archi Maulyda (Jurnal Kependidikan Penelitian Inovasi Pembelajaran, 2022)
This study aimed to identify, analyze, and reflect on vocational school leadership strategies for improving the quality of vocational education. The result achieved is forming the principal’s leadership strategy in improving the quality of education. This study used a qualitative approach so that the data collection was carried out through observation, document analysis, interviews, and questionnaires. This study can be developed to improve the quality of learning at the vocational school level in line with the implementation process. Academically, the results of this study can be used as a guideline for the development of vocational education management. The development of the school into an educational service organization with high-quality sustainability. The results show that the principal’s leadership strategy in improving the quality of education at SMK Negeri 1 Mataram includes articulation of the vision and mission of the school, leadership values of the leaders, awards in the school, social-emotional relationships of principals, and the quality of the “Link and Match” education in schools.